ENHANCEMENTR MODEL FRONTEND & BACKEND DEVELOPMEN OF SERVICE AND COMPLAINTS SYSTEMS AT UNIVERSITAS PEMBANGUNAN PANCA BUDI MEDAN - Purwanto, Dedi; Fadly, Yossi; Wijaya, Rian Farta; Senjari, Abdu Rangga (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
The University Quality Assurance Center is a work unit at Pembangunan Panca Budi University which has duties and functions in the field of Quality Assurance which provides direct services to students, lecturers and the public for complaints of academic and non-academic violations. Students, lecturers and the community need a service or facility to make it easier to submit questions and complaints related to academic and non-academic violations which of course hope to get answers directly from those who are experts in their fields. So far, The client application (Mobile Flutter) sends a request in HTTP Request Header format and the backend application (Web CodeIgniter) sends a response in JSON format, which then this JSON formatted data will be decoded and consumed by the mobile application. In sending requests, the mobile application also sends a token that is generated using the JWT (JSON Web Token) library which functions as an identification of the validity of the request sent. Without tokens, any system can send data and requests to our backend applications and that is very dangerous. For this reason, the token is generated when the user logs in at the start of the application. The token contains user data which is encrypted with a certain algorithm.